Clinical and laboratory parameters of confirmed and probable COVID-19 patients: experience from a tertiary care hospital of Bangladesh - Haque, Hasna Fahmima; Ahmed, AKM Shaheen; Habib, Samira Humaira; Sulzana, Maliha; Ghosh, Rahul Prasad; Shreya, Pradikta Das; Nessa, Azimun (BIRDEM Medical Journal, 2020)
Background: Severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), which was previously known as novel corona virus 2019 (2019-nCoV), causes corona virus disease 2019 (COVID-19). Since 8 March 2020, COVID -19 emerged in Dhaka city and rapidly spread throughout the country. This study evaluated the sociodemographic, clinical and laboratory parameters of confirmed and probable COVID-19 patients in a tertiary care hospital. Methods: This cross-sectional study was conducted in BIRDEM General Hospital, Dhaka, Bangladesh from May to October 2020. Adult (>18 years) patients having clinical symptoms and signs of COVID-19, irrespective of sex were included in this study. Diagnosis was confirmed by positive reverse transcriptase polymerase chain reaction (RT-PCR) for SARS-CoV-2 from nasopharyngeal samples of patients and the disease classification was done following national guidelines. Results: Total patients were 141with a mean age of 59.74±11.0 years; majority was from urban areas and there was male predominance. Diabetes mellitus (91.5%) and hypertension (75.2%) were common co-morbidities. Common clinical presentations were fever (100%), cough (97.2%), fatigue (88.7%) and shortness of breath (61.7%). Laboratory investigations revealed lymphopenia (73.8%), elevated level of C-reactive protein (94.3%) and positive D-dimer (99.4%). Chest x-ray showed bilateral shadows in 73.8% cases and 42.6% had COVID pneumonia in high-resolution computed tomography (HRCT) scan of chest. Nearly three-fifths (58.9%) of the study subjects had moderate COVID-19 and 70.92% patients were shifted to the COVID-dedicated hospitals. Conclusions: COVID-19 affects mostly the older males. Majority was diabetic and hypertensive. Common symptoms were fever, cough and respiratory distress. Common laboratory findings were lymphopenia, high CRP, positive D-dimer and bilateral shadows on lung imaging. Birdem Med J 2020; 10, COVID Supplement: 6-11